2003
DOI: 10.1081/jas-120021100
|View full text |Cite
|
Sign up to set email alerts
|

Cost, Morbidity, and Control of Asthma in Hungary: The Hunair Study

Abstract: Inhaled corticosteroids was the most frequent treatment prescribed for asthma patients in the study. However, patients reported substantial asthma-related morbidity. Children used more resources than adults, despite being classified as having better control. Patients with poor control of asthma symptoms incurred the highest societal cost, improving patient control may reduce cost to society by 40% or more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 10 publications
3
37
0
2
Order By: Relevance
“…These percentages equate to a gain of 2.6 h, 6 h and 6.7 h, respectively, in a 40-h working week for patients with at least well-controlled asthma [19]. Previous studies have also found significant direct and indirect costs associated with poorly controlled asthma [20,21]. The Hunair study [20] assessed 378 paediatric and 711 adult asthma patients in Hungary and found patients with poor asthma control had a significantly higher number of ER/hospital visits and general practitioner visits compared to patients with moderate or good control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These percentages equate to a gain of 2.6 h, 6 h and 6.7 h, respectively, in a 40-h working week for patients with at least well-controlled asthma [19]. Previous studies have also found significant direct and indirect costs associated with poorly controlled asthma [20,21]. The Hunair study [20] assessed 378 paediatric and 711 adult asthma patients in Hungary and found patients with poor asthma control had a significantly higher number of ER/hospital visits and general practitioner visits compared to patients with moderate or good control.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also found significant direct and indirect costs associated with poorly controlled asthma [20,21]. The Hunair study [20] assessed 378 paediatric and 711 adult asthma patients in Hungary and found patients with poor asthma control had a significantly higher number of ER/hospital visits and general practitioner visits compared to patients with moderate or good control. This study also showed that patients with, or parents of patients with, good asthma control missed significantly fewer work days compared with those with moderate or poor control.…”
Section: Discussionmentioning
confidence: 99%
“…Although this measure has not yet been validated, it simultaneously takes into account several markers of uncontrolled asthma (5). More recently, several studies have used this measure to evaluate asthma control (3)(4)(5)8,17).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, a number of markers have been separately considered to define the health status of asthmatic subjects (5) and, more recently, to evaluate asthma control (3,5,8,17). In the present study, we used a composite measure of asthma control according to a scheme based on GINA guidelines (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation